Implementasi Halal Awareness Bagi Mahasiswa FEBI IAIN Ponorogo Dalam Penggunaan Produk Skincare - Lutfia Rahma Dewi; Verbena Ayuningsih Purbasari (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The increasing use of skincare products among students requires awareness of the importance of the halalness of the products used. This study aims to understand the understanding, application, and impact of halal awareness in the use of skincare among students of the Faculty of Islamic Economics and Business IAIN Ponorogo. The research method used is qualitative with a field study approach. Data were obtained through interviews, observations, and documentation with students from various departments at FEBI. The results of this study indicate that although most students have understood the importance of product halalness, this awareness is still extrinsic, such as only relying on the halal logo without a deep understanding. The application of halal awareness includes the selection of halal ingredients, production processes that comply with sharia, product cleanliness, and halal certification for international products. As a result, students are more optical in choosing, buying, and using skincare products by considering aspects of halalness, safety, and product composition. It can be concluded that although halal awareness among students has begun to form, ongoing educational efforts are still needed to foster deeper intrinsic awareness, so that the principle of halalness is truly understood and applied consistently in daily consumption behavior.